Predictors of COVID-19 Vaccination Likelihood Among Reproductive-Aged Women in the United States. (May 2022) - Gutierrez, Sirena; Logan, Rachel; Marshall, Cassondra; Kerns, Jennifer; Diamond-Smith, Nadia
Objectives: Vaccination for COVID-19 is an effective method of preventing complications; however, studies suggest that public attitudes toward the vaccine are heterogeneous. The objective of our study was to identify predictors for low likelihood of COVID-19 vaccination among women in the United States and determine whether reasons for low intention were modified by race, ethnicity, or other characteristics to better understand the factors that shape attitudes toward the COVID-19 vaccine and help inform multilevel interventions. Methods: In January 2021, we used social media to recruit a cross-section of reproductive-aged women in the United States (N = 5269). Our primary outcome was self-reported low vaccination likelihood (responses of unlikely or very unlikely on a 5-item scale). Our secondary outcome was concerns influencing vaccination decision that participants selected from a list of 19 items. We estimated multivariable logistic regression models and controlled for respondents' sociodemographic characteristics. Results: Overall, race and ethnicity, educational attainment, health insurance type, annual household income, partnership status, and US region were associated with low vaccine likelihood. The adjusted odds of reporting low likelihood were 1.83 (95% CI, 1.45-2.32) times greater among non-Hispanic Black than among non-Hispanic White participants. Among pregnant or postpartum participants, breastfeeding status was the strongest predictor (adjusted odds ratio = 2.77; 95% CI, 2.02-3.79). Conclusions: Vaccine hesitancy and concerns may exacerbate existing COVID-19 health disparities in racial and ethnic groups and highlight the need to target messaging to specific populations, including pregnant and breastfeeding women, because these populations are at high risk for COVID-19 complications.